Effects of intra articular steroids, hyaluronic acid and combination of both among patients with knee osteoarthritis - B., Uganath Subash; M., Sundaramoorthy (International Journal of Research in Orthopaedics, 2019)
Background: Osteoarthritis (OA) is a common degenerative disorder of articular cartilage accompanied by hypertrophic changes of the bone. In the management of OA, though use of intra articular (IA) injection of steroids, hyaluronic acid (HA) separately plays an important role, their effects in terms of reducing pain, joint stiffness and movement restriction when it is used in combination remains a question. Hence this study was planned to assess the effects of HA and steroids alone with combination of both Ha and steroids. Methods: Prospective randomized comparative study, among patients with osteoarthritis knee attending the outpatient department of Orthopedics in a tertiary care hospital during January 2017 to May 2018, were included. Patients were randomized in three groups (steroids, HA and combination of both) and a total of 96 patients were included and the outcome was assessed by WOMAC scale. Statistical analysis was done using SPSS Version 20. Results: Pain and movement restriction, at the end of fourth week and pain, joint stiffness and movement restriction, were found to be statistically improved in combined steroids and HA group than the group with steroids alone. Similarly at the end of third month, pain and movement restriction were found to be statistically improved in combined steroids and HA group than HA group alone. Conclusions: This study demonstrates that HA together with corticosteroid provides pain relief, reduction of joint stiffness and helps in improving joint movements within three months after treatment.